Contribution of Arm Muscle Strength and Reaction to Straight Punches in Boxing Sports - Widuri Jais; Surisman; Candra Kurniawan; Dwi Priyono (Universitas PGRI Palembang, 2025)
This study aims to determine the contribution of arm muscle strength and reactionto straight punches in boxing at Sasana A 23 BC Bandar Lampung, both individually and collectively. This research is correlational research. The population of this study was 20 boxing athletes at the 23 BC Bandar Lampung gym. In this research, the sample collection method was total sampling. Datawere collected using tests and measurements with instruments in the form of a push and pull dynamometer for the arm muscle strength variable, whole body reaction for the reaction variable, and the straight punch test for the straight punch variable. The data analysis technique uses product- moment correlation analysis through prerequisite tests for normality and linearity. The research results showed that there was (1) a contribution between arm muscle strength andstraight punches, with a value of rx1.y = 0.607 > r(0.05)(28) = 0.374, and the contribution amount was 26.9%; (2) there is a contribution between the reaction to a straight punch, with a value of rx2.y = 0.447 > r(0.05)(28) = 0.374, and the magnitude of the contribution is 20%; and (3) there is a contribution between arm muscle strength and the reaction to a straight punch, with a calculated F value > F table (21.244 > 3.354), and the contribution amount is 61.1%.